The Effectiveness of Mobile Application as an Alternative of Health Education Media for Adolescents in the Middle School (Indian Journal of Forensic Medicine & Toxicology, 2020)
Adolescent health problems are still becoming major issues in health issues such as smoking behavior,drugs, and free sex. Improving health school age and adolescent is prioritized in promotive and preventiveefforts. One of them is done through the school health effort. The purpose of this study was to determinethe effectiveness of mobile applications as a health education media for adolescents in secondary schoolstowards adolescent knowledge and attitudes about health, compared to printed media. This type of researchis quasi experimental research with a two group comparison pretest-posttest design. There were significantmean differences in knowledge, attitudes and skills before and after getting an intervention using the mobileapplication media (p = 0.000). There were significant mean differences in knowledge, attitudes and skillsbefore and after getting an intervention using the My Health Report Card (p = 0.000). There was a significantmean difference in knowledge, where the mean score of knowledge was higher in the group using the mobileapplication media compared to using the My Health Report Card (p = 0.000). There are no differences in theattitudes and attitudes of groups who use the mobile application media and who use the My Health ReportCard.